Cardiac atrial appendage stem cells engraft and differentiate into cardiomyocytes in vivo: A new tool for cardiac repair after MI. (15th December 2015) - Fanton, Yanick; Robic, Boris; Rummens, Jean-Luc; Daniëls, Annick; Windmolders, Severina; Willems, Leen; Jamaer, Luc; Dubois, Jasperina; Bijnens, Eric; Heuts, Nic; Notelaers, Kristof; Paesen, Rik; et al.
Abstract: Background: This study assessed whether autologous transplantation of cardiac atrial appendage stem cells (CASCs) preserves cardiac function after myocardial infarction (MI) in a minipig model. Methods and results: CASCs were isolated from right atrial appendages of Göttingen minipigs based on high aldehyde dehydrogenase activity and expanded. MI was induced by a 2 h snare ligation of the left anterior descending coronary artery. Upon reperfusion, CASCs were intramyocardially injected under NOGA guidance (MI-CASC, n = 10). Non-transplanted pigs (MI, n = 8) received sham treatment. 3D electromechanical mapping (EMM) and cardiac MRI were performed to assess left ventricular (LV) function. MI pigs developed LV dilatation at 2 months (2 M), while in the MI-CASC group volumes remained stable. Global LV ejection fraction decreased by 16 ± 8% in MI animals vs 3 ± 10% in MI-CASC animals and regional wall thickening in border areas was better preserved in the MI-CASC group. EMM showed decreased viability and wall motion in the LV for both groups POST-MI, whereas at 2 M these parameters only improved in the MI-CASC. Substantial cell retention was accompanied by cardiomyogenic differentiation in 98 ± 1% of the transplanted CASCs, which functionally integrated. Second harmonic generation microscopy confirmed the formation of mature sarcomeres in transplanted CASCs. Absence of cardiac arrhythmias indicated the safety of CASC transplantation. Conclusion: CASCs preserve cardiac function by extensive engraftment and cardiomyogenic differentiation. Our data indicate the enormous potential of CASCs in myocardial repair.